A Comparative Analysis of an East Sakhalin Ainu folktale collected by Bronisław Piłsudski - Elia Dal Corso (Annali di Ca’ Foscari. Serie orientale, 2022)
This contribution presents a linguistic analysis of an East Sakhalin Ainu folktale collected by Bronisław Piłsudski in 1903. The author bases their analysis on two different versions of the text, which Piłsudski compiled himself using a cyrillic-script-based and a latin-script-based transcription for Ainu. Taking into account two versions of the folktale where different scripts are used proves insightful with regards to phonetics and phonology and, thanks to Piłsudski’s painstakingly accurate transcription, allows for investigation despite the lack of a backup audio recording. Starting from Piłsudski’s originals, the author provides a re-transliteration of the text, following modern standard conventions for Ainu, and a morphemic analysis. A discussion of the most salient grammatical aspects of the informant’s language fol-lows and a comparison with neighboring West Sakhalin Ainu dialects is drawn.